(untitled) - Edward Hughes (London, 1995)
The book is divided into four parts. The first part introduces the general electrical principles required by all and is followed by parts introducing electronic systems and power systems. The final part dealing with general principles has extended the introduction to electric circuits as well as extending the coverage of a.c. network analysis. The second part, dealing with Electronics, has been emphasized the systems instead of the components. At the same time, new systems have evolved and some consideration is given to A/D and D/A converters and to fibreoptics. The chapters dealing with power electronics have been extended, thus permiting a reduction in the number of rotating machines to be included. The close overlap of interests between power and electronic systems becomes apparent with the development of control systems. This book contains a complete introduction to electrical and electronic engineering as practised towards the end of the century
Keywords: electrical engineering,electronics